Corporate Tax in Nepal: Effective Burden (1975 – 2000) - Kandel, Puspa (NRB Economic Review, 2001)
The paper calculates and examines the effective burden of the corporate tax in Nepal over the period 1975 – 2000. The paper finds that the statutory tax rate is not the only factor that affects the burden of tax. Rather, inflation and many other variables affect the burden of tax borne by the capital income. Additionally, while the effective tax rate has gone down significantly over the last 25 years, the paper finds that the effect tax rate for debt-financed project have increased.